Characteristics of machining data and machine learning models - A case study - Natarajan, Elango; Fiorna, Vxynette; Al-Talib, Ammar Abdulaziz Majeed; Elango, Sangeetha; Gnanamuthu, Ezra Morris Abraham; Sarah Atifah, Saruchi (Institution of Engineering and Technology, 2023)
Advancement of technologies in computing such as internet of things, cloud computing, and artificial intelligence drive manufacturing industries to adopt and implement automation in production. One of the key technologies or preferable methods to increase the productivity is implementing prediction models or machine learning (ML) algorithms in production. This article is aimed to show a comprehensive review on AI implementation in machining of materials, and to present methodology in prediction model development. The characteristic of experimental data and the key attributes in the model development are presented and discussed with a case study.